Some Results on Preconditioned Mixed-Type Splitting Iterative Method. (3rd December 2013) - Wang, Guangbin; Tan, Fuping
Abstract : We present a preconditioned mixed-type splitting iterative method for solving the linear systemA x = b, whereA is a Z-matrix. And we give some comparison theorems to show that the rate of convergence of the preconditioned mixed-type splitting iterative method is faster than that of the mixed-type splitting iterative method. Finally, we give one numerical example to illustrate our results.